2014
DOI: 10.3126/ajms.v6i3.11088
|View full text |Cite
|
Sign up to set email alerts
|

Serum electrolytes and lipid profiles in non-insulin dependent diabetes mellitus patients

Abstract: Background: Diabetes mellitus and hyperlipidemia are the most common metabolic disorder affecting the people all over the world. Hyperglycemia is considered a primary cause of diabetic vascular complications and is associated with impaired electrolytes in some of the metabolic dysfunctions is not clear. Aim: The purpose of this study was conducted to investigate the relationship among diabetes mellitus, lipid profiles and electrolytes (Na+, K+ and Cl-). Methods: In the sera of 85 non insulin-dependent diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
2
7
2
Order By: Relevance
“…In present study we have found significantly increased levels of Sodium in Case group (Table 1). Similar findings are reported by Kavelaars et al and Danowsky TS et al 10,11 However, contradictory findings, i.e., hyponatraemia in diabetes mellitus, are reported by Namama Talabani, McNair P et al and George Liamis et al 4,12,13 Poorly controlled DM may lead to the development of hypernatremia. 5 Depending upon the balance between the hyperglycemiainduced water movement out of the cells lowering sodium, and the glucosuria-induced osmotic diuresis increasing sodium, serum sodium concentration is variable in patients with uncontrolled DM.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In present study we have found significantly increased levels of Sodium in Case group (Table 1). Similar findings are reported by Kavelaars et al and Danowsky TS et al 10,11 However, contradictory findings, i.e., hyponatraemia in diabetes mellitus, are reported by Namama Talabani, McNair P et al and George Liamis et al 4,12,13 Poorly controlled DM may lead to the development of hypernatremia. 5 Depending upon the balance between the hyperglycemiainduced water movement out of the cells lowering sodium, and the glucosuria-induced osmotic diuresis increasing sodium, serum sodium concentration is variable in patients with uncontrolled DM.…”
Section: Discussionsupporting
confidence: 65%
“…3 Diabetes mellitus (DM) is amongst those diseases which show frequent disturbances of electrolytes and acid -base relations, especially in patients with deranged renal function and other end-organ injury, mal-absorption syndromes, acid-base imbalances and multiple drug regimens and medications for diabetes management. [4][5][6][7] The knowledge and insight of the disease process and its management, would create the way for 'pathophysiologydirected therapy', leading to prevention of the several adverse effects associated with acid-base and electrolyte disorders and their management.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Wang in China revealed significantly higher proportion of hyperkalemia and hypokalemia among the diabetics in contrary to our results which showed no difference between the proportions of hypokalemia in comparison to the control population. 16 Talabani found no differences in the mean level of potassium, 26 whereas geographically closer to our country Ugwuja in Nigeria and Oyewole in SierraLeone reported lower mean level of potassium in diabetics than in control subjects. 14,27 In our study, the rate of hyponatremia among diabetic patients was similarly high as that of hyperkalemia (45.33% versus 48%).…”
Section: Kalemia Natremia and Chloremiacontrasting
confidence: 51%
“…14,24,26,27 Among the diabetic population, the observed alterations in the electrolytes levels were not correlated with the plasma glucose level. However the highest kalemia value was found in the group of glycaemia >2g/L (group III), the group with glycaemia between 1.2-2g/L (group II) exhibited a lower mean value of potassium than the group of glycaemia <1.2 g/L (group I).…”
Section: Kalemia Natremia and Chloremiamentioning
confidence: 86%
See 1 more Smart Citation